2010
DOI: 10.1111/j.1538-7836.2010.04065.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the post‐thrombotic syndrome with non‐invasive venous examinations in patients 6 weeks after a first episode of deep vein thrombosis

Abstract: To cite this article: Tick LW, Doggen CJM, Rosendaal FR, Faber WR, Bousema MT, Mackaay AJC, van Balen P, Kramer MHH. Predictors of the post-thrombotic syndrome with non-invasive venous examinations in patients 6 weeks after a first episode of deep vein thrombosis. J Thromb Haemost 2010; 8: 2685-92.Summary. Background: Post-thrombotic syndrome (PTS) is a chronic complication of deep vein thrombosis (DVT) affecting a large number of patients. Because of its potential debilitating effects, identification of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 42 publications
0
78
0
8
Order By: Relevance
“…7,8,47,51,73,75 Residual thrombosis after treatment of DVT has also been shown to be a predictor of PTS. 27,28,62,76 In patients with a first episode of DVT, the risk of PTS was 1.6-fold higher (95% CI, 1.0-2.5) in those with residual proximal thrombosis compared with those without this finding. 62 A recent study by Comerota et al 76 documented a statistically significant correlation between residual thrombus after CDT and PTS severity.…”
Section: Risk Factors Apparent During Dvt Treatment and Follow-upmentioning
confidence: 77%
See 2 more Smart Citations
“…7,8,47,51,73,75 Residual thrombosis after treatment of DVT has also been shown to be a predictor of PTS. 27,28,62,76 In patients with a first episode of DVT, the risk of PTS was 1.6-fold higher (95% CI, 1.0-2.5) in those with residual proximal thrombosis compared with those without this finding. 62 A recent study by Comerota et al 76 documented a statistically significant correlation between residual thrombus after CDT and PTS severity.…”
Section: Risk Factors Apparent During Dvt Treatment and Follow-upmentioning
confidence: 77%
“…A study by Tick et al 46 reported that DVT in the femoral and iliac veins was associated with an increased risk of PTS compared with popliteal vein thrombosis (RR, 1.3; 95% CI, 1.1-1.6), perhaps because of more rapid and complete resolution of thrombosis in distal vein segments. 62 In a study by Labropoulos et al 67 of patients with a first episode of acute DVT, PTS was more frequent and more severe when the iliac vein was occluded in conjunction with other veins. In the previously noted study of PTS after pregnancy-related DVT, the strongest predictor of PTS was proximal thrombosis that occurred postpartum (OR, 6.3; 95% CI, 2.0-19.8).…”
Section: Dvt Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Among known age-dependent changes in the immune system, the dynamic of the memory T-cell compartment seems particularly striking. After an initial marked increase in the first decade of life, memory T-cell frequencies reach a plateau and remain stable throughout the adulthood.…”
Section: Circulation Researchmentioning
confidence: 99%
“…40 A recent prospective study showed that patients with proximal DVT had a relative risk of developing PTS of 2.3 (95% confidence interval [CI], 1.0-5.6) compared with patients with IDDVT, although the latter were not free from this late complication. 41 In conclusion, it should be recognized that, because of the scarcity of prospective, blind, nonintervention studies, both the natural history of IDDVT and its clinical relevance are still not clearly understood. In general, however, it can be said that the proximal extension of IDDVT, although at rates much lower than previously reported, is not rare, and the disease-with or without extension-is not always free from acute and late complications.…”
Section: Late Sequelaementioning
confidence: 99%